2015
DOI: 10.14260/jemds/2015/1067
|View full text |Cite
|
Sign up to set email alerts
|

Role of Multidetector Computed Tomography in Evaluation of Pediatric Abdominal Tumors

Abstract: BACKGROUND:A wide variety of tumors may affect pediatric abdomen, which arise from various organs. These may be benign or malignant. OBJECTIVES: (1) To assess the role of computed tomography in the evaluation of pediatric abdominal tumors-in localization and characterization. (2) To illustrate the common pediatric abdominal masses. MATERIALS AND METHODS: 30 patients in the age group 0 to 18 years with suspected abdominal mass underwent non contrast and contrast enhanced computed tomography. The lesions were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Majority of patients were seen in 0-5 years age group followed by 11-15 years age group with a M:F ratio of 1.8:1. Nagaraju RM et al [5] observed majority of abdominal masses in age range of 0-5 years. Abdominal lump was the commonest clinical complaint (71.4%) followed by pain abdomen (53.6%).…”
Section: Discussionmentioning
confidence: 98%
“…Majority of patients were seen in 0-5 years age group followed by 11-15 years age group with a M:F ratio of 1.8:1. Nagaraju RM et al [5] observed majority of abdominal masses in age range of 0-5 years. Abdominal lump was the commonest clinical complaint (71.4%) followed by pain abdomen (53.6%).…”
Section: Discussionmentioning
confidence: 98%